Natural products as promising therapeutics for fine particulate matter–induced skin damage: a review of pre-clinical studies on skin inflammation and barrier dysfunction - Jeayeng, Saowanee; Kwanthongdee, Jaturon; Jittreeprasert, Ratima; Runganantchai, Kankanich; Naksavasdi, Kalayaporn; Rirkkrai, Rosarin; Wongcharoenthavorn, Varisara; Mahikul, Wiriya; Chatsirisupachai, Anyamanee (PeerJ, 2025)
Background Particulate matter less than 2.5 µm (PM2.5) is a significant air pollutant and is linked to an increased risk of health conditions, including skin diseases. The skin, as the first barrier and the largest organ, is primarily damaged by PM2.5 through different pathways. Several studies have shown that PM2.5 upregulates inflammatory responses through the excessive production of reactive oxygen species (ROS) and several inflammatory cytokines, leading to PM2.5-induced skin damage. The ROS/mitogen-activated protein kinase (MAPK) and Cyclooxygenase-2-Prostaglandin E2 (COX2/PGE2) inflammatory pathways are activated by free radical scavenging and phase II detoxification. Natural products have been suggested as therapeutic agents for mitigating PM2.5-induced skin damage. Objectives We elaborate on the mechanisms of action of natural products and their functions as protectants against environmental skin diseases. This review highlights the optimal doses of natural products for clinical study, which may benefit dermatologists, molecular biologists, clinicians, and healthcare professionals in preventive and alternative medicine. Methodology The available scientific literature published between 1999 and 2024 was searched using PubMed and Google Scholar. Multiple keywords related to the topic were used. Only 41 of the screened articles were chosen for this review, as they were the most relevant publications on the topic of the preventive advantages of natural products and specific pathways targeting PM2.5-induced skin injury. All relevant articles meeting the criteria of being original full articles and written in English were included. Results This review summarized the natural products, including phenolic/polyphenolic compounds and flavonoids, that can act as anti-inflammatory and antioxidant agents by protecting the skin against oxidative stress, inhibiting enzymes that promote free radical formation, enhancing antioxidant enzyme activity, and reducing overall ROS formation. Several natural products have demonstrated efficacy in alleviating intracellular ROS, oxidative stress, mitochondrial dysfunction, autophagy, and apoptosis caused by PM2.5. In addition, phytochemical agents support the restoration of the skin wound healing process and muscle contraction impaired by environmental pollutants, such as PM2.5 and UV rays. Conclusion This review highlights promising natural agents that can protect against environment-mediated health problems by focusing on their mechanisms of action. Particular emphasis is placed on antioxidant and anti-inflammatory compounds, including sulforaphane, hesperidin, quercetin, catechin, diphloroethohydroxycarmalol, resveratrol, and ginsenoside, which have become interesting candidates as nutraceuticals due to their potential to reduce reliance on conventional medicines. However, the low stability and bioavailability of natural products remain significant challenges to their clinical use; therefore, further research and development are warranted.
Keywords: Antioxidant; Natural products; Skin damage; Inflammation; Skin barrier dysfunction; Particulate matter 2.5